Membrane properties and esterase activity of synovial lining cells: further evidence for a mononuclear phagocyte subpopulation. Issue 3 (June 1982) - Edwards, J C; Sedgwick, A D; Willoughby, D A
Abstract : Recent work in our laboratory with mouse radiation chimeras suggests that the macrophage type of synovial lining cell is derived from bone marrow. Further evidence for including this cell type in he mononuclear phagocyte system is now presented. Rosette formation with IgG coated sheep red cells, immunofluorescent staining for surface Ia antigens, and nonspecific esterase staining all show the presence in the synovial lining of a subpopulation of cells carrying these markers. The proportion of such cells in the lining is very variable, as is the proportion of 'type A' cells recognised with the electron microscope.